LEVEL OF KNOWLEDGE AND PHYSICAL ACTIVITY WITH BLOOD SUGAR LEVELS IN DIABETES MELLITUS SUFFERERS AT THE PRACTICE OF INDEPENDENT DOCTOR EKA MARLIANA - Kurnia, Lilis; Aminah, Siti (HEARTY, 2025)
Background: Diabetes mellitus is a health condition characterized by metabolic disorders due to lack of production and function of the hormone insulin, which causes an increase in blood sugar levels in the urine (Syamsiah, 2017). The World Health Organization (WHO, 2015) notes that around 10 million people worldwide suffer from diabetes mellitus. Indonesia is ranked fourth with the highest number of sufferers after India, China and the United States. According to the Indonesian Ministry of Health's Basic Health Research Data (Riskesdas) (2013), the number of Diabetes Mellitus sufferers in Indonesia reached 9.1 million people, with 90% of them suffering from type 2 diabetes (Soegondo, 2012). The Indonesian Statistics Agency recorded that the prevalence of type 2 diabetes mellitus in urban areas was 14.7%, while in rural areas it was 7.2%. Banten Province is one of the provinces in Indonesia with a high prevalence rate of Diabetes Mellitus. Knowledge is defined as facts, truth, or information obtained through experience or learning (Arisma et al., 2017). Meanwhile, physical activity is body movement that involves skeletal muscles, requires energy, and can provide health benefits (Anggraeni & Alfarisi, 2018). Research Objective: This aims to analyze the relationship between the level of knowledge and physical activity and blood sugar levels in patients diabetes mellitus at the Independent Doctor's Practice. Research Method: This research design is analytical descriptive, focusing on the relationship between independent and dependent variables. Research Results: The results of statistical tests using questionnaire sheets filled in by respondents (diabetes mellitus patients) showed P values of 0.048 and 0.000. Thus, it can be concluded that there is a significant relationship between the level of knowledge and physical activity and blood sugar levels in diabetes mellitus patients at the Eka Marliana Independent Doctor's Practice.